Effects of Nickel Contamination on Nutrient Contents of Daffodil (Narcissus poeticus L. c.v. “Ice Folies”) - Arzu ÇIĞ; Füsun Gülser; Tuğba Hasibe Gökkaya; Gülçinay Başdoğan (International Journal of Secondary Metabolite, 2017)
The objective of this study was to determine the effects of nickel on nutrient contents of daffodil (Narcissus poeticus L. c.v. “Ice Folies”) in nickel contaminated media. This research was carried out in a completely randomized experimental design with three replications in greenhouse conditions. Four different doses of nickel   (control, 25 mg kg-1, 50 mg kg-1, 75 mg kg-1) were applied to each pot having 500 g soil:sand mixture in 2:1 ratio. The distillate water was used in irrigation and ½  hoagland solution was applied for fertilization. At the end of experiment the highest K, Mg and Ca contents of daffodil bulbs were obtained as 0.90 %, 0.91 % and 2.72 % in control respectively. The highest Fe (27.42 mg kg-1), Cu (7.62 mg kg-1), and Zn (20.99 mg kg-1)  were in 50 mg kg-1, 75 mg kg-1 and 25 mg kg-1 nickel applications respectively. Similarly the highest K, Mg and Ca contents of daffodil leaves were obtained as 2.2 %, 1.72 % and 5.87 % in control.  The highest Fe contents (66.62 mg kg-1) was in 25 mg kg-1 nickel application, while Cu (41.29 mg kg-1) and Zn contents (41.04 mg kg-1) were in 75 mg kg-1 nickel application. Nickel applications increased micronutrients contents of daffodils except manganese.